RETRACTED: Changes in Tobacco Dependence and Association With Onset and Progression of Use by Product Type From Wave 1 to Wave 3 of the Population Assessment of Tobacco and Health (PATH) Study. Issue 3 (8th July 2022) - Strong, David R; Pierce, John P; White, Martha; Stone, Matthew D; Abrams, David B; Glasser, Allison M; Wackowski, Olivia A; Cummings, K Michael; Hyland, Andrew; Taylor, Kristie; Edwards, Kathryn C; Silveira, Marushka L; et al.
Abstract: Introduction: This study examined trajectories of tobacco dependence (TD) in relation to changes in tobacco product use and explored the effects of product-specific adding, switching, or discontinued use on dependence over time. Aims and Methods: Data were analyzed from the first three waves of the Population Assessment of Tobacco and Health (PATH) Study, a nationally representative, longitudinal study of adults and youth in the United States. Data included 9556 Wave 1 (2013/2014) adult current established tobacco users who completed all three interviews and had established use at ≥2 assessments. Groups included cigarettes-only users, e-cigarettes-only users, cigars-only users, hookah-only users, any smokeless-only users, cigarette + e-cigarette dual users, and multiple product users. A validated 16-item scale assessed TD across product users. Results: Wave 1 e-cigarette-only users' who maintained exclusive e-cigarette use increased levels of TD through Wave 3 as did those who added or switched to another product. Wave 1 multiple product users' TD decreased across waves. TD for all other Wave 1 user groups remained about the same. For Wave 1 cigarette-only smokers, switching to another product or moving to a pattern of no established use was associated with lower levels of TD than smokers whose use stayed the same. Movement to no established use of any tobacco product was consistently associated with lower TD for all other product users. Conclusions: Except for Wave 1 e-cigarette-only users, TD among US tobacco product users was stable over time, with daily users less likely to vary from baseline. Implications: The level of TD among most US tobacco users was stable over the first three waves of the PATH Study and trends in levels of TD were predominantly unrelated to changes in patterns of continued product use. Stable levels of TD suggest a population at persistent risk of health impacts from tobacco. Wave 1 e-cigarette users, including those maintaining exclusive e-cigarette use, experienced increasing levels of TD over time, perhaps because of increases in quantity or frequency of their e-cigarette product use or increasing efficiency of nicotine delivery over time.